TRANSMISSION-BASED PRECAUTION EDUCATION ON KNOWLEDGE AND HANDWASHING PRACTICES IN SCHOOL-AGED CHILDREN IN THE ERA OF PANDEMI COVID-19 - Lingga Curnia Dewi; Ika Nur Pratiwi; Rr Dian Tristiana (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Washing hands is important to prevent various infectious diseases, including Covid-19. School-age children are a population at risk who must practice proper hand hygiene. This study aims to examine the effect of Transmission-Based Precaution (TBP) on knowledge and practice of hand washing in school age children. A total of 20 schoolchildren living in Islamic boarding schools participated in this study. Education is carried out in one meeting. The data was collected by filling out a questionnaire on knowledge and hand washing practices pre and post education. The results showed that providing TPB education increased knowledge about hand washing (p = 0.010), but it was not significant for hand washing practices (p = 0.282). Increasing knowledge should also pay attention to the attitude of school children in hand washing behavior. The process of providing education will be more embedded in school children after repeatedly implementing hand washing properly. The teachers and classmates involved can participate in hygiene education to encourage the hand washing behavior of students in areas at high risk of infectious diseases, especially Covid-19.